Glucose uptake and transport in contracting, perfused rat muscle with different pre-contraction glycogen concentrations. - Hespel, P (1990)
1. Glucose uptake and transport, muscle glycogen, free glucose and glucose-6-phosphate concentrations were studied in perfused resting and contracting rat skeletal muscle with different pre-contraction glycogen concentrations. Rats were pre-conditioned by a combination of swimming exercise and diet, resulting in either low (glycogen-depleted rats), normal (control rats) or high (supercompensated rats) muscle glycogen concentrations at the time their hindlimbs were perfused. 2. Compared with control rats, pre-contraction muscle glycogen concentration was approximately 40% lower in glycogen-depleted rats, whereas it was 40% higher in supercompensated rats. Muscle glycogen break-down correlated positively (r = 0.76; P less than 0.001) with pre-contraction muscle glycogen concentration. 3. Glucose uptake during contractions was approximately 50% higher in glycogen-depleted hindquarters than in control hindquarters; in supercompensated hindquarters it was 30% lower. When rats with similar muscle glycogen concentrations were compared, glucose uptake in hindquarters from rats that had exercised on the preceding day was approximately 20% higher than in hindquarters from rats that had not exercised on the preceding day. 4. Muscle membrane glucose transport, as measured by the rate of accumulation of 14C-3-O-methylglucose in the contracting muscles, was 25% lower in supercompensated than in glycogen-depleted muscles at the onset as well as at the end of the 15 min contraction period. 5. Intracellular concentrations of free glucose and glucose-6-phosphate were higher at rest and during the entire 15-min stimulation period in supercompensated muscles than in glycogen-depleted muscles, and glucose uptake during contractions correlated negatively with free glucose (r = -0.52; P less than 0.01) as well as with glucose-6-phosphate (r = -0.49; P less than 0.01) concentrations. 6. It is concluded that: (a) The rate of glucose uptake in contracting skeletal muscle is dependent on the pre-contraction muscle glycogen concentration. Regulating mechanisms include limitations of membrane glucose transport as well as of glucose metabolism. (b) Contractions on the preceding day have a stimulating effect on glucose uptake during contractions of the same muscles on the next day.